Kedudukan Anak Dalam Perkawinan Batal Karena Wali Tidak Sah Di Pangkalan Susu - Muhammad Syauqy (Journal Smart Law, 2023)
Marriage annulment is a request by a husband, wife, or both of their families to the Islamic Courts because a defect in the conditions or pillars of marriage. An annulled marriage declared never occured since the contract took place. This problem occurred in the marriage of Anizar and Joko Prayetno, residents of Sei Siur village, Pangkalan Susu district. The marriage was declared void by several ustadz and KUA officers, because they considered Anizar's father was not qualified as guardian. From these problems, it is necessary to conduct research to find out the review of Marriage Law and Compilation of Islamic Law regarding invalid marriages and status of lineage resulting from invalid marriages. The research was conducted using field research methods with a qualitative approach. Datas were obtained using interview techniques, observation and documentation in the form of Marriage Law and Compilation of Islamic Law, along with supporting data taken from relevant sources such as law books, fiqh books and journals. The datas are then grouped and analyzed. As a result, the marriage of Anizar and Joko Prayetno cannot be said to be invalid because Anizar's father never denied his lineage, so the marriage was valid. Regarding the lineage of the child, the lineage of the child in a void marriage is connected to his parents, and his father is eligible as the guardian.